Commercial plasma donation and individual health in impoverished rural China - Xi Chen (Health Economics Review, 2014)
Background: Blood collection following nonstandard operations largely increases the risks of infectious diseases through cross-contamination. Commercial plasma donation and the resulting HIV/AIDS and hepatitis C epidemics in central China in the 1990s killed more than one million people. Many blood banks have since moved to more remote southwest provinces, which have become new suppliers of blood plasma. Methods: Utilizing a primary longitudinal survey, this paper documents commercial plasma donation and estimates its negative health impacts in impoverished rural China using individual fixed effect models. Both the linear regression model and generalized linear models are utilized. Results: Attracted by the financial compensation, a majority of plasma donors are poor, and bear grave consequences of malnutrition and worse health status as a result of unhygienic and frequent donations. Donating plasma is associated with a .83 standard deviation (SD) decline in self-rated health, a .54 SD lower self-rated health relative to peers in their age group, a .74 SD higher chance of being infected with hepatitis, lacking of strength to conduct farm work, and experiencing appetite loss, fatigue, nausea, and vomiting. Discussion: Results indicate an urgent need of more comprehensive and effective interventions on hepatitis screening, diagnosis, and treatment among plasma donors in less developed contexts to eliminate cross-infection of infectious diseases and possible widespread epidemic in the future. Besides, we should encourage voluntary plasma donation to gradually crowd out paid donation.
Keywords: 330; Paid plasma donation; Poverty; Panel data; HIV/AIDS; Hepatitis; Health status